Theological Ethical Study of the Role of Parents in Educating Children in the Gmim Marturia Ratatotok Congregation - Arina, Hein; Suoth, Vanny; Sambuaga, Syalomita (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2024)
The research focuses on the crucial role of parents in shaping the moral and spiritual development of children in the congregation, as well as close collaboration between parents and the Church in instilling positive values ​​and providing spiritual guidance to children. This research aims to determine the ethical awareness and involvement of parents in educating children within the GMIM Marturia Ratatotok congregation, emphasizing the theological and ethical dimensions of the role of parents. The research method used is qualitative, using observation data collection, interviews, literature studies, and data analysis. This research explores the perspectives and benefits of involving parents and children in natural environments. Research findings emphasize the importance of the active role of parents in shaping the moral and spiritual character of children in the congregation. The research results show that parental involvement rooted in Christian values ​​is crucial to promoting children's well-being and building a societal foundation of truth. So, it can be concluded that the active involvement of parents in children's education within the GMIM Marturia Ratatotok congregation is significant for developing children's character and spiritual growth. The implications of this research emphasize the need to prioritize parental involvement and support and strong collaboration between parents and the Church. This research recommends special programs designed to increase parental awareness and involvement in children's education and develop effective strategies to strengthen collaboration between parents and the Church in instilling Christian values.